Stereocontrolled protein surface recognition using chiral oligoamide proteomimetic foldamers1. Issue 4 (16th April 2015) - Azzarito, Valeria; Miles, Jennifer A.; Fisher, Julie; Edwards, Thomas A.; Warriner, Stuart L.; Wilson, Andrew J.
<x xml:space="preserve">Abstract</x> An oligoamide helix mimicking foldamer with well-defined conformation is shown to recognize its target protein hDM2 in a manner that depends upon the composition, spatial projection and stereochemistry of functional groups appended to the scaffold.